Stephanostomum talakitok n. sp. (Digenea: Acanthocolpidae) from the golden trevalley, Gnathanodon speciosus (Perciformes: Carangidae), from Ningaloo Reef, Western Australia - Bray, Rodney A.; Cribb, Thomas H. (Zootaxa, 2006)
A new species, Stephanostomum talakitok n. sp., is described from the golden trevally Gnathanodon speciosus, Ningaloo Reef, Western Australia. It has 36 (34ñ40) circum-oral spines and the vitellarium reaches to no less than 10ñ17% of the hindbody length from the ventral sucker. It differs from other species of Stephanostomum with these characteristics by combinations of the gradual diminution of the circum-oral spine size to a small mid-ventral spine, the contiguous gonads with no intervening vitelline follicles, the sucker-ratio and various other ratios, including the distance between the ventral sucker and the ovary and the distance the cirrus-sac reaches into the hindbody, both as a proportion of body length.